EFFICIENCY ASSESSMENT OF ARABIC GUM FOR HEAVY METAL REMOVAL FROM POLLUTED WASTEWATER - Shalikh , Halah M.; Majeed, Majid R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The" aim" of this study is to use the natural adsorbents which consist of gum arabic as absorbents for plant products to remove heavy metals from industrial wastewater and standard aqueous solutions with a prepackaged bed column (PBC) technique based on a Box-Wilson design". The gum arabic was modified into carbonated gum by oven maville at 300°C. The influence of were studied: pH value, contact time, and removal efficiency estimation using a packed layer column which gives the best" heavy metal removal" performance."The study showed the removal efficiency tests of charred gum arabic absorbers that the best removal from industrial wastewater were: 80%, 68.75% and 90.7% for lead (Pb), cobalt (Co) and cadmium (Cd) respectively, at pH 5-6.5 and contact time. 0.25 - 4.30 hours. While from the standard aqueous solutions, they were: 82.5%, 71.4% and 91% for Pb, Co and Cd respectively, at pH 5 - 6.5 and contact time 0.25 - 4.30 hours. In addition, other pollutants of charred gum arabic such as total dissolved solids (TDS) and electrical conductivity (E.C) have been reduced in industrial wastewater. The carburizing degumming efficiency showed significant differences between removal of heavy metals at (p≤ 0.05).